Learning from Project Failure: Globalization Lessons for an MNC. (14th December 2015) - Chanda, Sasanka Sekhar; Ray, Sougata
Abstract : We study a multinational corporation's (MNC) failure in implementing a firm‐wide information technology system (ITS) project. To counter heightened competitive pressures, the MNC sought to improve its supply chain responsiveness by implementing the ITS project. However, since the headquarters (HQ) personnel lacked nuanced understanding of the micro issues in the subsidiaries, their design efforts turned out to be inadequate. Organizational practices that restrict member behavior to recipes from past knowledge served to amplify the problem—by disfavoring cooperation. Our study suggests a need to rethink the notion of the HQ as the design place. Further, there is a case for subsidiary personnel being afforded a greater say in design of changes to their work processes, given their higher exposure to process variety. This may offset the HQ‐subsidiary power imbalance noted in prior literature. © 2015 Wiley Periodicals, Inc .